Plant design and operations - Sutton, Ian (Gulf Professional Publishing, 2017)
Ian Sutton provides practical guidance on the design, operation, and maintenance of process facilities. The book is based on years of hands-on experience gathered during the design and operation of a wide range of facilities in many different types of industry including chemicals, refining, offshore oil and gas, and pipelines.
Keywords: Chemical plants -- Design and construction.; elektronické knihy; electronic books